Ubiquitination and SUMOylation in Telomere Maintenance and Dysfunction - Yalçin, Zeliha; Selenz, Carolin; Jacobs, Jacqueline J. L. (Frontiers in Genetics, 2017)
Telomeres are essential nucleoprotein structures at linear chromosomes that maintain genome integrity by protecting chromosome ends from being recognized and processed as damaged DNA. In addition, they limit the cell’s proliferative capacity, as progressive loss of telomeric DNA during successive rounds of cell division eventually causes a state of telomere dysfunction that prevents further cell division. When telomeres become critically short, the cell elicits a DNA damage response resulting in senescence, apoptosis or genomic instability, thereby impacting on aging and tumorigenesis. Over the past years substantial progress has been made in understanding the role of post-translational modifications in telomere-related processes, including telomere maintenance, replication and dysfunction. This review will focus on recent findings that establish an essential role for ubiquitination and SUMOylation at telomeres.